If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 13)(x + -3) = 0 Reorder the terms: (13 + 2x)(x + -3) = 0 Reorder the terms: (13 + 2x)(-3 + x) = 0 Multiply (13 + 2x) * (-3 + x) (13(-3 + x) + 2x * (-3 + x)) = 0 ((-3 * 13 + x * 13) + 2x * (-3 + x)) = 0 ((-39 + 13x) + 2x * (-3 + x)) = 0 (-39 + 13x + (-3 * 2x + x * 2x)) = 0 (-39 + 13x + (-6x + 2x2)) = 0 Combine like terms: 13x + -6x = 7x (-39 + 7x + 2x2) = 0 Solving -39 + 7x + 2x2 = 0 Solving for variable 'x'. Factor a trinomial. (-13 + -2x)(3 + -1x) = 0Subproblem 1
Set the factor '(-13 + -2x)' equal to zero and attempt to solve: Simplifying -13 + -2x = 0 Solving -13 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -2x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -2x = 0 + 13 -2x = 0 + 13 Combine like terms: 0 + 13 = 13 -2x = 13 Divide each side by '-2'. x = -6.5 Simplifying x = -6.5Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-6.5, 3}
| Y=38+7.7x | | log(x+13)-log(2)=log(3x+3) | | 7x=28000000 | | 0.60x+0.85*30=0.30*97 | | 2(6x-13)= | | log(x+13)-log(2)=log(2x+3) | | 43-2[6+(3+2)]= | | 0.03x+0.15(70)=0.15(82) | | 2x+x+6=8 | | Sin(2x)cos(x)=sin(x)cos(2x) | | -4/5(-19/16) | | 12+3[5+(4-2)]= | | |-5|= | | 0.0003x^2+2x+300= | | |11|= | | |-3|= | | 2ly+4x-x^2=0 | | 0.30x+22.00=112.00 | | -384+n=12 | | 6a-11=8+2a | | (2x-5)=255 | | 4x-10+2x=5+6x-14 | | -182+14=n | | 318=2(9-3w)+2w | | 3/10x=1/5=-2 | | 1-(8/k^3)=0 | | n+(-6)=22 | | 444=2(8-4w)+2w | | 153+n=17 | | 2/7y-8=11 | | 15-(x+7)=7x-8 | | 7/8-9/-8/2 |